Preliminaries - RAMOS HOLGUÍN, BERTHA; Peñaloza Rallón, Anna Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In the preliminaries, you can find information about the editorial committee, page numbers, and journal.